Colonial survey and native landscapes in rural South Africa, 1850-1913 : the politics of divided space in the Cape and Transvaal - Braun, Lindsay Frederick (African social studies series, 2014)
"In Colonial Survey and Native Landscapes in Rural South Africa, 1850 - 1913, Lindsay Frederick Braun explores the technical processes and struggles surrounding the creation and maintenance of boundaries and spaces in South Africa in the nineteenth and early twentieth centuries."--Publisher's description